Utilization of common grasses by goats in two seasons - Islam, M.; Alam, M. R. (Asian-Australasian Association of Animal Production Societies, 1996)
The effect of feeding freshly-cut common grasses on growth performance of Black Bengal goats during the pre-monsoon and pre-dry season was evaluated. Four castrated goats of 5-6 months age with a mean initial body weight were 11.17 and 10.23 kg for pre-monsoon and pre-dry season respectively, were used as experimental animal. Nutrient component, intake of different nutrients and its effect on body weight changes were determined. Common grass harvested during the pre-monsoon season contained higher nitrogen (15.6 g/kg) and less DM (196.8 g/kg) than the grass harvested in pre-dry season where nitrogen was 12.8 g/kg and DM was 454.9 g/kg. Intake of DM, OM, N, and NDF were 73.12 g, 67.12 g, 964.68 mg and 50.14 g/kg W0.75 respectively in pre-monsoon were higher than those in pre-dry season at p < 0.01 level of significance. Higher (p < 0.01) growth (35.71 g/day) rate was found in pre-monsoon season. It may concluded that grasses grown during the pre-monsoon season was higher nitrogen value and appeared to be more palatable.